Värdering av kvävet i organiska gödselmedel - Orvendal, Jon (2008)
Within agriculture it is important to optimize the use of nitrogen, not only from an economic point of view but also to minimize damage to the environment. This can sometimes be difficult, especially within organic farming. Organic farmers are using increasing amounts of waste products from the food industry to cover their nitrogen needs. These different organic fertilizers release nitrogen at different rates and under specific soil conditions. Because of this, it would be beneficial to have a standardized method to measure the amount and rate of nitrogen mineralization from organic fertilizers.